Efficiency enhancement of ZnO dye-sensitized solar cell using platinum nanoparticles prepared by sparking process - K. Hongsith (2018)
Copyright © 2015 American Scientific Publishers. All rights reserved. The platinum nanoparticles as a counterelectrode in ZnO dye-sensitized solar cells were studied. The film was prepared by simple and cost-effective sparking technique onto fluorine-doped tin oxide glass substrate as various thickness compared with the platinum counterelectrode which generally prepared by thermal reduction method. The thickness of platinum film was controlled by number of sparking cycles for 5, 15, 25, 35, 50 and 100 cycles under normal atmospheric pressure. The surface morphology and thickness were characterized by Field emission Scanning Electron Microscopy and crystal structure was investigated by X-ray diffractometry. It was found that the power conversion efficiency of the 15 cycles sparking platinum films reached 2.13% which was significantly higher than 1.81% of the reference cell. This efficiency enhancement can be explained by the arising of short-circuit photocurrent due to the increasing of the active surface area and decreasing of charge transfer resistance. Thus, platinum nanoparticles prepared by sparking process can be an alternative counterelectrode for ZnO dye-sensitized solar cells.